Mitochondrial stress disassembles nuclear architecture through proteolytic activation of PKCδ and Lamin B1 phosphorylation in neuronal cells: implications for pathogenesis of age-related neurodegenerative diseases - Charli, Adhithiya; Chang, Yuan-Teng; Luo, Jie; Palanisamy, Bharathi; Malovic, Emir; Riaz, Zainab; Miller, Cameron; Samidurai, Manikandan; Zenitsky, Gary; Jin, Huajun; Anantharam, Vellareddy; Kanthasamy, Arthi; et al. (Frontiers in Cellular Neuroscience, 2025)
Mitochondrial dysfunction and oxidative stress are central to the pathogenesis of neurodegenerative diseases, including Parkinson’s, Alzheimer’s and Huntington’s diseases. Neurons, particularly dopaminergic (DAergic) ones, are highly vulnerable to mitochondrial stress; however, the cellular and molecular mechanisms underlying this vulnerability remain poorly understood. Previously, we demonstrated that protein kinase C delta (PKCδ) is highly expressed in DAergic neurons and mediates apoptotic cell death during neurotoxic stress via caspase-3-mediated proteolytic activation. Herein, we further uncovered a key downstream molecular event of PKCδ signaling following mitochondrial dysfunction that governs neuronal cell death by dissembling nuclear architecture. Exposing N27 DAergic cells to the mitochondrial complex-1 inhibitor tebufenpyrad (Tebu) induced PKCδ phosphorylation at the T505 activation loop accompanied by caspase-3-dependent proteolytic activation. High-resolution 3D confocal microscopy revealed that proteolytically activated cleaved PKCδ translocates to the nucleus, colocalizing with Lamin B1. Electron microscopy also visualized nuclear membrane damage in Tebu-treated N27 cells. In silico analyses identified threonine site on Lamin B1 (T575) as a phosphorylation site of PKCδ. Interestingly, N27 DAergic cells stably expressing a PKCδ cleavage-resistant mutant failed to induce nuclear damage, PKCδ activation, and Lamin B1 phosphorylation. Furthermore, CRISPR/Cas9-based stable knockdown of PKCδ greatly attenuated Tebu-induced Lamin B1 phosphorylation. Also, studies using the Lamin B1T575G phosphorylation mutant and PKCδ-ΔNLS-overexpressing N27 cells showed that PKCδ activation and translocation to the nuclear membrane are essential for phosphorylating Lamin B1 at T575 to induce nuclear membrane damage during Tebu insult. Additionally, Tebu failed to induce Lamin B1 damage and Lamin B1 phosphorylation in organotypic midbrain slices cultured from PKCδ−/− mouse pups. Postmortem analyses of PD brains revealed significantly higher PKCδ activation, Lamin B1 phosphorylation, and Lamin B1 loss in nigral DAergic neurons compared to age-matched healthy controls, demonstrating the translational relevance of these findings. Collectively, our data reveal that PKCδ functions as a Lamin B1 kinase to disassemble the nuclear membrane during mitochondrial stress-induced neuronal death. This mechanistic insight may have important implications for the etiology of age-related neurodegenerative diseases resulting from mitochondrial dysfunction as well as for the development of novel treatment strategies.